2011
DOI: 10.1038/nature10374
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic jet activity from the tidal disruption of a star by a massive black hole

Abstract: Supermassive black holes have powerful gravitational fields with strong gradients that can destroy stars that get too close, producing a bright flare in ultraviolet and X-ray spectral regions from stellar debris that forms an accretion disk around the black hole. The aftermath of this process may have been seen several times over the past two decades in the form of sparsely sampled, slowly fading emission from distant galaxies, but the onset of the stellar disruption event has not hitherto been observed. Here … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
686
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(751 citation statements)
references
References 25 publications
53
686
0
2
Order By: Relevance
“…We conclude with several important implications of our results. First, the velocity and kinetic energy of the outflow in ASASSN14li are significantly lower than inferred for the two relativistic γ-ray TDEs previously detected in the radio (Figure 6), which represent  a few percent of the TDE population (Bloom et al 2011;Burrows et al 2011;Zauderer et al 2011;Mimica et al 2015). Although the TDE sample with detected radio emission is small, this is reminiscent of the same relation observed in Type Ib/c core-collapse supernovae (Type Ib/c SNe) and long-duration gamma-ray bursts (LGRBs), in which a small fraction of events (LGRBs: ∼1% by volumetric rate) produce energetic relativistic outflows while the bulk of the population (Type Ib/c SNe) produces lower energy non-relativistic outflows ( Figure 6; Margutti et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude with several important implications of our results. First, the velocity and kinetic energy of the outflow in ASASSN14li are significantly lower than inferred for the two relativistic γ-ray TDEs previously detected in the radio (Figure 6), which represent  a few percent of the TDE population (Bloom et al 2011;Burrows et al 2011;Zauderer et al 2011;Mimica et al 2015). Although the TDE sample with detected radio emission is small, this is reminiscent of the same relation observed in Type Ib/c core-collapse supernovae (Type Ib/c SNe) and long-duration gamma-ray bursts (LGRBs), in which a small fraction of events (LGRBs: ∼1% by volumetric rate) produce energetic relativistic outflows while the bulk of the population (Type Ib/c SNe) produces lower energy non-relativistic outflows ( Figure 6; Margutti et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical calculations indicate that most tidal disruption events (TDEs) lead to superEddington fallback, which in turn drives outflows (Rees 1988;Evans & Kochanek 1989;Strubbe & Quataert 2009;Guillochon & Ramirez-Ruiz 2013). The discovery of luminous radio emission from the γ-ray TDE Sw J1644+57 revealed the formation of a relativistic jetted outflow (Zauderer et al 2011;Berger et al 2012), but such events represent at most a few percent of the TDE population (Bloom et al 2011;Burrows et al 2011;Zauderer et al 2011;Mimica et al 2015). While the sample of well-studied TDE candidates has expanded greatly in recent years, direct evidence for outflows in the bulk of the TDE population, discovered through optical, ultraviolet (UV), and X-ray observations, has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The areal densities of type Ibc supernovae(SNe Ibc; Berger et al 2003;Soderberg et al 2006b), low-luminosity GRBs(LLGRB; Soderberg et al 2006a;Barniol Duran et al 2015), and tidal disruption events(TDEs) without strong jets Holoien et al 2015;van Velzen et al 2016) are so small that it will be quite rare to detect them as false positive transients. Although off-axis long GRBs(LGRBs; van Eerten et al 2010; Ghirlanda et al 2014) and tidal disruption events with strong jets (TDE(jet); Burrows et al 2011;Zauderer et al 2011;Berger et al 2012) can be false positive transients, they will be identified earlier through their optical counterparts or can be filtered by identifying their host galaxies since the typical distance of these events is far beyond the detectable distance of the GW networks.…”
Section: False Positives: Extragalactic Radio Transients and Variablesmentioning
confidence: 99%
“…This is not seen in BH X-ray binaries in the thermal state and may be intrinsic to TDEs. Although the TDE candidate Swift J164449.3+573451 also showed large fast variability, its origin is not so clear and can be produced in the jet [15] or due to fast variations in the mass accretion rate as above [25]. The fast variability is seldom studied for other TDE candidates, due to their lack of X-ray data of high quality.…”
Section: -P2mentioning
confidence: 99%
“…Most TDE candidates more or less show the above properties. Swift J164449.3+573451 and Swift J2058.4+0516 are two exceptions, which are hard X-ray transients and are probably due to observation of a relativistic jet pointed toward us [15][16][17].…”
Section: Introductionmentioning
confidence: 99%